การตรวจวัดแก๊สเรดอนในน้ำบาดาลบริเวณ 3 จังหวัดชายแดนภาคใต้โดยวิธีการกัดรอย ทางนิวเคลียร์ THE INESTIGATION OF RADON IN GROUNDWATER OF THREE SOUTHERN PROVINCE USING NUCLEAR TECHIQUE - อนันตนุกูลวงศ์, โรสลีนา (Srinakharinwirot University Journal of Sciences and Technology, 2021)
This research investigated the intensity of radon gas in groundwater. Collecting groundwater samples in the three southern border provinces, namely Pattani, Narathiwat and Yala, totaling 45 samples. by using a set of alpha ray detector devices on a CR-39 plastic sheet and collecting water samples until the maturity of 40 days. Expand the nuclear pathway with sodium hydroxide solution concentration 6.25 N at a temperature of 60๐C for 24 hours. The alpha radiation density of the CR-39 plastic sheet can be used to calculate the concentration of radon gas in groundwater. The result showed that the maximum radon gas concentration from Narathiwat, Pattani and Yala were 9.7 0.188738 Bq/l, 10.6244 0.163452 Bq/l and 4.24975 0 Bq/l. The minimum radon gas concentration of each province were 3.43 0.49677 Bq/l, 3.6 0.163452 Bq/l and 0.653808 0 Bq/l. The average concentration of radon gas were 6.55333 Bq/l, 5.526906 Bq/l and 1.639259 Bq/l respectively. Finally, the water all samples from Pattani and Yala has radon gas concentration lower than in the standard from the USEPA standard (11 Bq/l) [1-2]